Association of preoperative platelet counts with in-hospital mortality in patients with acute type A aortic dissection: a retrospective single-center study - Yifei Zhou; Yifei Zhou; Wuwei Wang; Quan Liu; Quan Liu; Hongwei Jiang; Rui Fan; Xin Chen; Xin Chen (Frontiers in Cardiovascular Medicine)
BackgroundThis study aimed to investigate the relationship between preoperative platelet (PLT) count levels and postoperative in-hospital death and mid-term survival in patients with acute type A aortic dissection (ATAAD).MethodsA total of 341 ATAAD patients who underwent surgery between January 2019 and December 2023 were enrolled in this retrospective study. Preoperative PLT count levels were compared between the two groups for whether in-hospital death occurred. Then, patients were divided into two groups according to the optimal cutoff value by the maximum Youden index (184.5), and confounders were adjusted by multiple models to confirm whether low PLT count was an independent risk factor for in-hospital death after surgery. Kaplan–Meier method was used to draw the survival curve for the mid-term follow-up.ResultsPatients who suffered in-hospital death had lower preoperative PLT count levels. After grouping by PLT count, patients in the low PLT count group exhibited higher in-hospital mortality (16.9% vs. 5.5%; P = 0.004). Univariate logistic regression analysis indicated that ATAAD patients with low PLT count were prone to death during hospitalization [odds ratio (OR): 4.549; 95% confidence interval (CI): 1.515–13.654, p < 0.05]. After adjustment for the potential confounders, low PLT count remained an independent risk factor with postoperative in-hospital death (OR: 3.443, 95%CI: 1.400–8.468, p < 0.05). Mid-term follow-up showed that there was a significant difference in overall survival between different PLT count groups (HR: 3.154; 95%CI: 1.495–6.654, p < 0.05).ConclusionA lower level of preoperative PLT count was an independent risk factor for in-hospital death in patients with ATAAD and had a lower survival rate at mid-term follow-up.